Who Said It Better? A Test of Wording Differences in the MedWatch "Toll-Free Statement" for Consumer Reporting of Side Effects in Direct-to-Consumer Television Advertisements. (March 2016) - Aikin, Kathryn J.; O'Donoghue, Amie C.; Sullivan, Helen W.; Betts, Kevin R.; Squire, Claudia
Background: A toll-free statement alerting consumers how to report side effects to the US Food and Drug Administration (FDA) is required for both prescription drug labeling and direct-to-consumer (DTC) print ads. Because of different regulatory requirements between these materials (the Toll-free Number for Reporting Adverse Events on Labeling for Human Drug Products Rule [TFNR] versus the FDA Amendments Act [FDAAA], respectively), the wording of this statement differs. We studied how statement wording for reporting side effects to FDA in DTC television ads affects comprehension of product risks and benefits, comprehension of and memory for the toll-free statement, and perceived statement clarity. Methods: Participants viewed 1 of 8 mock prescription drug television ads that varied the wording and placement of the toll-free statement, and then responded to a questionnaire. Results: The FDAAA statement was more noticeable, clear, and more participants were able to recall and recognize its correct purpose. Comprehension of product risk and benefit information did not differ based on statement wording. Conclusions: Findings suggest that the FDAAA toll-free statement wording is superior to that of the TFNR.